A comparative study to assess the knowledge, attitude and practice regarding tuberculosis among the male and female TB patients in district Amritsar - Sadana, Pooja; Verma, Vishal; Singh, Tejbir; Deepti, S. S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Lack of knowledge about tuberculosis could have an effect on the patients who seek health care services and continue the disease transmission within the public. Hence, the study was conducted in Amritsar district to assess knowledge, attitude and practice towards transmission and prevention of Tuberculosis. Methods: The study was conducted on 326 patients registered with district tuberculosis centre, Amritsar. Information was collected with reference to knowledge, attitude, and practice regarding TB. Results: A total of 228 patients participated in the study. 72.4% had heard of tuberculosis before being diagnosed, with significant gender difference (p=0.016). 19.3% were afraid to disclose the disease to others. The relation between fear of disclosing the disease and gender was found to be statistically significant (p=0.011). 23.5% male vs 8.3% females were worried about finances, which was found to be statistically significant (p=0.002). Regarding the practices, 72.4% of the patients used separate utensils. In response to stigma 9.2% patients had isolated themselves from other members and 34.6% had discontinued their work and there was significant gender difference seen with both these practices (p=0.0001). Conclusions: There were lot of unfavourable attitude and practices regarding TB. More male patients had heard of tuberculosis. Due to social stigma more males had isolated themselves and discontinued their work as compared to females. Females were worried that other family members may not get the disease.